Radiation Characteristic Improvement of X-Band Slot Antenna Using New Multiband Frequency-Selective Surface - Elham Moharamzadeh (International Journal of Antennas and Propagation)
A new configuration of frequency-selective surfaces (FSSs) is designed and presented with multiresonance characteristics which covers all of the frequency domain of X-band from 8 to 12 GHz. The proposed FSS comprises three conductor-based split ring resonators, connected together. In this design, two unit cells of the FSS with different lengths are employed side by side to design the FSS. The FSS is used to enhance the gain of the new designed triangle slot antenna at X-band. The proposed FSS is analyzed by using reflected-wave unit-cell box method. The single, double, and array of the FSS cells are studied. Next, the designed FSS along with the antenna is analyzed. The measurement and simulated results of the impedance and radiation characteristics, especially the increment of the gain, are presented.